2005
DOI: 10.1016/j.aml.2003.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant singular fourth-order boundary value problems

Abstract: Existence results are presented for the nonresonant singular fourth-order boundary value problemwhere f : [0, 1] × (0, ∞) → (0, ∞) is continuous and β < π 2 . Existence is established via the fixed point theorem in cones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…A lot of research has been conducted where many numerical schemes have been developed for solving boundary-value problems [1][2][3][4][5][6][7][8][9][10][11]. Many of these schemes are based on discretization of the space and finite difference approximations of the derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been conducted where many numerical schemes have been developed for solving boundary-value problems [1][2][3][4][5][6][7][8][9][10][11]. Many of these schemes are based on discretization of the space and finite difference approximations of the derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Problems of the form (1.1), for example, are used to model such phenomena as the deflection of an elastic beam supported at the endpoints. Most of the available literature on fourth-order boundary value problems, for instance [1][2][3][4][5], showed that the equations had at least single and multiple positive solutions. Recently, Lin [6] considered the following fourth-order boundary value problem:…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that an assumption of type (1.1) is completely novel for fourth-order differential problems, while an assumption of type (1.2), when it is used, usually needs additional conditions on the nonlinear term. Here, no asymptotic condition at infinity on g is required, and the existence of non-trivial solutions is also obtained for problems where the results in the literature, such as those in [1,10,12,13], cannot be applied (see Remark 4.4). This paper is arranged as follows.…”
Section: Introductionmentioning
confidence: 94%
“…The existence of at least one non-zero solution for nonlinear fourth-order differential problems has been investigated in several works by using different approaches such as fixed point theorems, lower and upper solutions methods, critical point theory and so on (see, for example, [1,10,12,13]). In these cited papers, under suitable assumptions on the nonlinear term, several types of existence results have been obtained.…”
Section: Remark 44mentioning
confidence: 99%
See 1 more Smart Citation